REACT-Based Acid-Base LKPD Development for Class XI SMA/MA Students - Husna Rosma; Andromeda Andromeda (Universitas Negeri Padang, 2022)
ABSTRACT One of the determining factors for the success of learning in the classroom is the use of learning media that can help educators convey messages and subject matter to students effectively and efficiently. Based on the questionnaire analysis, SMAN 16 Padang and SMAN 1 Gunung Talang, information was obtained that most of the class XI students said that the difficulty in understanding chemistry lessons was one of the reasons for the limited use of teaching materials. Therefore, the purpose of this study is to produce teaching materials in the form of REACT-based acid-base Student Worksheets (LKPD) for class XI Senior High School which are valid and practical and to determine the level of validity and practicality of the REACT-based acid-base worksheets that have been developed. The method used in the development or Research and Development (R&D). The results of this study are REACT-based worksheets on acid-base materials for class XI Senior High School developed through a 4-D development model with the stages of define, design, develop, and disseminate. Valid and practical LKPD.